The Healthy Weight Paradox: Unmasking High Dyslipidemia Prevalence in Normoweight Adults with Normal Waist Circumference - Raden Chantika Nur Annisa (Archives of The Medicine and Case Reports, 2026)
The reliance on body mass index (BMI) as the sole anthropometric indicator for cardiovascular risk is increasingly debated. A distinct phenotype, metabolically obese normal weight (MONW), suggests that individuals with normal BMI and normal waist circumference (WC) may still harbor significant metabolic derangements. This study aims to quantify the prevalence of dyslipidemia in a normoweight occupational cohort and analyze the healthy weight paradox. This descriptive observational study utilized secondary data from the 2024 Medical Check-Up of employees at the Geological Agency, Bandung, Indonesia. A total of 142 subjects met the strict inclusion criteria: BMI 18.5–22.9 kg/m² and normal waist circumference (<90 cm for men, <80 cm for women). Lipid profiles—Total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and Triglycerides (TG)—were analyzed. Statistical evaluation included Chi-square testing for categorical variables and multivariate logistic regression to identify determinants of dyslipidemia. Despite normal anthropometry, 54.93% (n=78) of subjects exhibited dyslipidemia. The most prevalent abnormalities were borderline high TC (24.65%) and mixed dyslipidemia (20.42%). A significant gender disparity was observed, with 62.0% of males exhibiting dyslipidemia compared to 38.1% of females (p < 0.05). Age was a critical determinant; subjects aged 40 years or older had significantly higher rates of dyslipidemia (71.62%) compared to those younger than 40 years (p < 0.01). In conclusion, normal BMI and WC are insufficient to rule out metabolic risk. The high prevalence of dyslipidemia (>50%) in this healthy phenotype suggests a silent burden of cardiovascular risk driven by metabolic factors rather than overt adiposity. Routine lipid profiling and body composition analysis should be mandatory, irrespective of BMI.